2016
DOI: 10.1037/lhb0000200
|View full text |Cite
|
Sign up to set email alerts
|

The interdependence of perceived confession voluntariness and case evidence.

Abstract: The current research investigated the mechanisms by which perceptions of confession evidence both influence and are influenced by perceptions of other case evidence using the theoretical framework of coherence-based reasoning (CBR). CBR posits that ambiguity and uncertainty are eschewed by artificially imposing consistency between pieces of evidence through bidirectional reasoning: Inferences about evidence lead to a preferred verdict, which in turn radiates backward to influence the perception of evidence. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…People do not adequately discount confession evidence even when the confessions are perceived to have been coerced by police (Kassin & Sukel, 1997); even when told that the defendant suffers from a mental illness or was under duress (Henkel, 2008); even when the defendant is a juvenile (Redlich, Ghetti, & Quas, 2008; Redlich, Quas, & Ghetti, 2008); even when the confession was reported secondhand by an informant motivated to lie (Neuschatz, Lawson, Swanner, Meissner, & Neuschatz, 2008; Neuschatz et al, 2012); and, even at times, when the confession is flat-out contradicted by exculpatory DNA (Appleby & Kassin, 2016). The disadvantages are so compelling at this stage that people perceive coercive interrogation tactics that elicit a confession as more acceptable, and the confession as more voluntary, when other incriminating evidence (that may or may not be independent of the confession; see above) suggests the defendant’s guilt (Greenspan & Scurich, 2016; Shaked-Schroer, Costanzo, & Berger, 2015).…”
Section: Stage 4: Wrongful Convictionsmentioning
confidence: 99%
“…People do not adequately discount confession evidence even when the confessions are perceived to have been coerced by police (Kassin & Sukel, 1997); even when told that the defendant suffers from a mental illness or was under duress (Henkel, 2008); even when the defendant is a juvenile (Redlich, Ghetti, & Quas, 2008; Redlich, Quas, & Ghetti, 2008); even when the confession was reported secondhand by an informant motivated to lie (Neuschatz, Lawson, Swanner, Meissner, & Neuschatz, 2008; Neuschatz et al, 2012); and, even at times, when the confession is flat-out contradicted by exculpatory DNA (Appleby & Kassin, 2016). The disadvantages are so compelling at this stage that people perceive coercive interrogation tactics that elicit a confession as more acceptable, and the confession as more voluntary, when other incriminating evidence (that may or may not be independent of the confession; see above) suggests the defendant’s guilt (Greenspan & Scurich, 2016; Shaked-Schroer, Costanzo, & Berger, 2015).…”
Section: Stage 4: Wrongful Convictionsmentioning
confidence: 99%
“…Given the ubiquity of mental cross-over effects, it is not surprising that mutual influencing of different pieces of evidence occurs in the process of becoming convinced of the suspect's guilt. As such, the assimilation effect may well be part of the story-model hypothesis (Pennington & Hastie, 1992), or the coherence-based reasoning hypothesis mentioned earlier (see Greenspan & Scurich, 2016). In fact, the hypotheses at hand (assimilation, storymodel, coherence-based reasoning) stipulate the difficulty of thinking about whether or not the suspect has committed the crime.…”
Section: No Psychopathy Psychopathymentioning
confidence: 93%
“…Recent research suggests for example, that if the decision maker is convinced of the suspect's guilt, he will consider the evidence to be stronger, compared to when he judges the strength of the evidence outside of the context of a specific case. Greenspan and Scurich (2016) found that people who are convinced of the suspect's guilt perceive a disputable confession to be more voluntary than those who are not convinced. The evaluation of evidence strength may not only be influenced by the decision maker's conviction, but also by the presence of other pieces of evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Such unwarranted-and otherwise inexplicable-influences are observed, often incidentally, across a variety of research projects. For illustration, the undermining of a defendant's alibi results in stronger belief in the prosecution evidence (Smith et al 1996), increasing the strength of a prosecution witness's testimony results in lower judgments of police coercion during an interrogation (Greenspan & Scurich 2016), and learning that the suspect confessed to the crime increases the (erroneous) belief that his handwriting matches the writing on the note used in the robbery (Kukucka & Kassin 2014). In other words, evidence items will be under-or overweighted depending on their placement in the broader constellation of evidence.…”
Section: The Coherence Effectmentioning
confidence: 99%